2014
DOI: 10.1159/000356973
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Enamel Pellicle from Dental Erosion Patients

Abstract: Oral health is dependent upon a thin mobile film of saliva on soft and hard tissues. Salivary proteins adhere to teeth to form the acquired enamel pellicle which is believed to protect teeth from acid erosion. This study investigated whether patients suffering diet-induced dental erosion had altered enamel pellicles. Thirty patients suffering erosion were compared to healthy age-matched controls. Subjects wore a maxillary splint holding hydroxyapatite and human enamel blocks for 1 h. The acquired enamel pellic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 33 publications
5
50
0
11
Order By: Relevance
“…A similar amount was also used in previous studies [Cheaib and Lussi, 2011;Ionta et al, 2014]. This concentration is higher than the physiological concentration of mucin in vivo [Carpenter et al, 2014]; however, the rehardening effect did not differ from that one without mucin, in accordance with previous studies [Ionta et al, 2014]. In addition, apart from the presence of mucin in the RE-experiment, both artificial salivas tested behaved similarly to in situ human saliva and better than water.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A similar amount was also used in previous studies [Cheaib and Lussi, 2011;Ionta et al, 2014]. This concentration is higher than the physiological concentration of mucin in vivo [Carpenter et al, 2014]; however, the rehardening effect did not differ from that one without mucin, in accordance with previous studies [Ionta et al, 2014]. In addition, apart from the presence of mucin in the RE-experiment, both artificial salivas tested behaved similarly to in situ human saliva and better than water.…”
Section: Discussionsupporting
confidence: 84%
“…Clinically, the differences founded in salivary characteristics and in the composition of salivary pellicles might explain why some individuals show a high susceptibility for the development of erosive tooth wear compared to sound-tooth individuals with a similar exposition to acid [Wetton et al, 2007;Cheaib and Lussi, 2011;Hellwig et al, 2013]. A previous study found a reduction in statherin, mucin (MUC 5B), calcium, and total protein contents in salivary enamel pellicles of patients suffering from dental erosion [Carpenter et al, 2014]. In addition, it was demonstrated that, after exposition to acid, there were proteomic changes in the acquired dentine and enamel pellicle, with identification of some acid-resistant proteins, such as mucins [Delecrode et al, 2015a, b].…”
Section: Discussionmentioning
confidence: 96%
“…To have standardized conditions, pooled saliva from healthy subjects was used. Saliva from healthy subjects and patients with dental erosion do not differ in the total protein amount [Bardow et al, 2014;Carpenter et al, 2014], but the content of calcium and proteins is reduced in newly formed acquired pellicle on enamel in dental erosion [Carpenter et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…On the surface of the enamel, the acquired enamel pellicle has a protective effect against erosion; however, controversy remains regarding the fundamental interactions between the acquired enamel pellicle and early dietary erosion in vivo. In situ studies have demonstrated that the pellicle has varying erosion-modifying properties that depend on the exact structure and composition, especially with regard to thickness, and mineral and protein content [Hannig and Balz, 1999;Hannig and Joiner, 2006;Carpenter et al, 2014;Moazzez et al, 2014]. However, we have revealed more subtle superficial back-scattered OCT signal changes, not only from erosion but also from wiping the tooth with a damp cotton pledget, which resulted in significantly reduced back-scattered OCT signal intensity ( p = 0.02) after both orange juice rising and water rinsing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the impact of clinical variables influencing in vivo enamel OCT imaging is not clearly understood. Thus, quantitative detection of early enamel erosion using OCT in vivo is complicated by multiple interacting surface phenomena which are poorly defined, including the composition and function of the acquired enamel pellicle [Hannig et al, 2003;Carpenter et al, 2014;Moazzez et al, 2014], the degree of hydration of the dental hard tissue during imaging [Nazari et al, 2013;Chan et al, 2014], and the micro-textural changes of the curved enamel surface in vivo during erosion [Austin et al, 2015[Austin et al, , 2016. Therefore, carefully controlled clinical studies simulating early erosion are required to elucidate the optimal analytical techniques for imaging early erosive changes.…”
Section: © 2017 S Karger Ag Baselmentioning
confidence: 99%